Improved calculation method of reinforced concrete elements strength on inclined sections - Dovzhenko, Оksana; Pohribnyi, Volodymyr; Maliovana, Оlena; Karabash, Leonid (Academic journal Industrial Machine Building Civil Engineering, 2019)
Application boundaries of the truss analogy and disk model methods to the strength calculation of reinforced concrete flexural elements inclined sections are established. Areas of structures failure by virtual compressed element (inclined strip) and compressed zone over dangerous inclined crack under the shear force are determined. The criterion of minimum limit force, which is perceived by the elements, is applied. Influence of concrete class, relative shear span and transverse reinforcement intensity on elements strength based on variational method in plasticity theory is specified. The data concerning the values of the transverse reinforcement coefficient at the boundaries of the failure from shear within the inclined strip and compressed zone over the dangerous crack are obtained.